Increasing student engagement through parent invnnolvement - Labibah, Balqis Salma; Utami, Adnani Budi; Haque, Sayidah Aulia Ul (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
Education is an effort made intentionally to improve the quality of human resources by motivating and accommodating student learning activities. Students who are active in learning at school are needed as a form of smoothness in the learning process to obtain optimal learning outcomes. This study aims to determine whether there is a relationship between parental involvement and student involvement. Sampling using population study techniques, namely taking the entire population as research respondents. The results of the normality test of the distribution on the scale of parental involvement with student involvement against the One-Sample Kolmogorov Smirnov Test obtained sig 0.200 at p = (p> 0.05) meaning that the scale of parental involvement with student involvement is normally distributed. Based on the analysis of the hypothesis test using product moment correlation, it produces an rxy value = 0.321 with a significance value of 0.000 (p <0.01) which indicates that there is a very significant positive relationship between parental involvement and student involvement. This means that the more positive the parental involvement, the higher the student involvement.